Pengaruh Pandemi covid-19 dan Kinerja Keuangan terhadap Harga Saham Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Ulfa Krisda Yanti; Putu Eka Dianita Marvilianti Dewi (Universitas Pendidikan Ganesha, 2022)
ABSTRACTThe share price is a reflection of the value of an entity. If the company achieves good performance, of course it will attract investors. This study aims to examine the effect of Covid-19, ROA, NPM, and OPM on stock prices of telecommunications companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population of this study was obtained by using purposive sampling method on telecommunication companies listed on the Indonesia Stock Exchange. With this method obtained a sample of 4 companies. The analytical technique used is the paired sample t-test or the wilcoxon signed ranked test and multiple linear regression, while the hypothesis test uses a t-test with a significance level of 5%. Classical assumption testing used in this study includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test with SPSS application tools. Based on the research, the results showed that Covid-19 showed a difference before and after the Covid-19 pandemic on stock prices. Meanwhile, Return On Assets (ROA), Net Profit Margin (NPM) have a positive effect on stock prices with a significance level of <0.05 while Operating Profit Margin (OPM) has no significant effect on stock prices.Keywords : Covid-19, ROA, NPM, OPM, Share Price